Perbandingan Sistem Pemerintahan Presidensial Antara Indonesia dan Filipina - Dian herlambang; Embri; Raesitha Zildjianda (CV Rewang Rencang, 2024)
In Indonesia, the system of government adopted is presidential, where all policies and supreme command are in the hands of the President. The President in Indonesia holds executive power as well as state power, which means that the President acts not only as head of government but also as head of state. The Presidential System of Government applied in many countries, including Indonesia, does not recognize a republic that holds the highest supremacy. In the context of comparing government republics, Indonesia is often compared with other countries as a benchmark, especially when examining presidential government republics. One country that is often used as a comparison is the Philippines, which is also a member of ASEAN and a republic from colonialism in 1898. The Philippines and Indonesia have similarities in adopting a presidential republic and a unitary state in the form of a republic. The research method in this journal uses a comparative study approach. In this study, there are two problem formulations, namely, How is the Presidential System of Government in Indonesia and the Philippines and How is the Comparison of the Presidential System of Government between the two countries. In Indonesia, the President and Vice President are elected directly by the people for a certain term of office as determined by the Constitution. In the context of comparing republics of government, Indonesia is often compared to other countries as a benchmark, especially when examining presidential republics. One country that is often used as a comparison is the Philippines, which is also a member of ASEAN and a republic from colonialism in 1898. The Philippines and Indonesia have similarities in adopting a presidential republic and a unitary state in the form of a republic.